Synthesis gas production from glycerol steam reforming over alumina supported bimetallic Co-Ni catalyst - Cheng, C. K. (2011)
Glycerol,a carbohydrate substrate, is produced in large quantities by the burgeoning biodiesel industry.The opportunity to produce synthesis gas (H 2/CO mixture) from this bioprocessing residue by steam reforming is a potential advantage in the future integration of biorefineries with current petrochemical plants since syngas may be converted to clean fuels via the Fischer-Tropsch process.In this work, alumina supported catalysts comprising of bimetallic Co-Ni, alkaline earth oxide (MgO, CaO, SrO, BaO) doped Co-Ni and lanthanide oxide (Ce0 2, Pr203,Sm203) doped Co-Ni, were synthesized by wetness co-impregnation technique and assessed in a fixed-bed reactor over steam-to-glycerol ratio of 3.0<STGR12.0 andtemperatures of 773 to 823 K. Kinetic examination of glycerol steam reforming over Co-Ni catalyst gave an activation energy of 63.3 kJ mol'. Mechanistic models were evaluated on the basis of statistical adequacy and thermodynamic consistency.These criteria revealed that the reaction was best characterized by a Langmuir-Hinshelwood (LH) bimolecular model with associative adsorption of glycerol and steam on two different catalytic sites.Carbon deposition during the reaction appeared to be responsible for the loss in surface area and pore volume of the used catalysts.At least two types of carbonaceous species were evidenced on the catalyst a more reactive atomic carbon species deposited on the metal-support interface while a less reactive carbon of the polymeric nature,was located on the alumina support. Interestingly,the acidity of doped Co-Ni catalysts decreased with Pauling electronegativity of the dopants.In addition, the metal surface area of all doped catalysts (0.8 to 1.1 m2 gcat1) was considerably higher than the undoped catalyst (0.7 m2 gcat ' )while lanthanide oxide doped-catalysts also increased the degree of reducibility of Co-Nj catalyst.This study also disclosed that although carbon deposition is inevitable,lanthanide oxide-doped catalysts decreased the carbon laydown (8-20%).The carbonresilient property of these catalysts was further substantiated through longevity tests. In the final phase of the work, H 2 and CO2 were individually added as carbon gasifying agents during the reforming.In particular,CO 2 could be tuned at selected partial pressure and temperature to produce a syngas with more suitable H 2 :CO ratio for the Fischer-Tropsch synthesis.